Validating the Space-Time Model for Infrequent Snow Avalanche Events Using Field Observations from the Columbia and Rocky Mountains, Canada. Issue 1 (1st February 2016) - Sinickas, Alexandra; Jamieson, Bruce
ABSTRACT: Avalanche runout distance and return period estimates are essential to snow avalanche risk assessment for hazard mapping and mitigation design. We present a validation of the Space-Time (ST) model, a statistical model that expresses runout distance as a function of return period. The validation is based on field observations of tree damage and tree ring data of infrequent (1:5 to 1:100 year return period) avalanches from 34 paths in the Canadian Rocky and Columbia Mountains. While the ST model has been applied successfully for a longer return period (>100 year) runouts in one path, our validation showed that it does not independently estimate infrequent runout distances with sufficient accuracy for hazard mapping and mitigation design. As with estimating extreme runouts, it should be used in combination with other methods. The model was found to perform differently across mountain ranges, and tended to estimate runout distance downslope of those observed in the field.